Emergent chirality in achiral liquid crystals: insights from molecular simulation models of the behaviour of bent-core mesogens. Issue 13 (8th December 2018) - Lintuvuori, Juho S.; Yu, Gary; Walker, Martin; Wilson, Mark R.
ABSTRACT: We report insights into the behaviour of achiral bent-core liquid crystals using (a) atomistic models of the PnOPIMB series of mesogens and (b) simple coarse-grained models that demonstrate the spontaneous transfer of chirality between molecules by preferential selection of chiral conformations. The models explain the unusual phenomena that chiral interactions can lead to an increase in chirality (decrease in pitch) of a bulk cholesteric liquid crystal when doped with an achiral material. We demonstrate also that chiral interactions are sufficiently strong to induce nanophase separation of an achiral mesogen within a liquid crystal phase, into nanodomains of opposite handedness by preferential selection of conformations that are instantaneously chiral (i.e. nanophase separation ofR andS conformations of a molecule that is strictly achiral). We suggest that this unusual behaviour contributes to the templating of chiral structures in bulk phases and, hence, to many of the extraordinary properties of bent-core mesogens that include the formations of helical nanofilaments and the chiral dark conglomerate phase. Graphical Abstract: